Evaluating Alternative Techniques Floodplain Mapping - Wolman, M. Gordon (Water Resources Research, 1971)
A variety of techniques is available for providing information on the frequency and extent of flooding in river valleys. These techniques include the use of physiography, pedology, vegetation, occasional floods, regional floods of selected frequency, and flood profiles and backwater curves. Preliminary estimates of costs suggest that these range from a low of $1–4/mile of channel to a high of $400–1000/mile of channel. All estimates of flood hazards and damages contain significant uncertainties deriving from the variability and uncertainty of the estimates of hydrologic, hydraulic, and social phenomena. An accelerating demand for information coupled with recognition of the inherent element of judgment in any determination of flood or damage zones suggests additional emphasis on the adoption of different mapping techniques appropriate to the needs of different locations.
Keywords: Ouvrage_Collectif_Numéro1

At Risk: Natural Hazards, People's Vulnerability and Disasters - Wisner, Benjamin Goodwin; Blaikie, Piers; Cannon, Terry; Davis, Ian J. (1994)
Many disasters are a complex mix of natural hazards and human action. At Risk argues that the social, political and economic environment is as much a cause of disasters as the natural environment. Published within the International Decade of Natural Hazard Reduction, this book suggests ways in which both the social and natural sciences can be analytically combined through a 'disaster pressure and release' model. Arguing that the concept of vulnerability is central to an understanding of disasters and their prevention or mitigation, the authors explore the extent and ways in which people gain access to resources. Individual chapters apply analytical concepts to famines and drought, biological hazards, floods, coastal storms, and earthquakes, volcanos and landslides - the hazards that become disasters'. Finally, the book draws practical and policy conclusions to promote a safer environment and reduce vulnerability.
MAG ID: 2058329721